New spectrophotometric techniques for the estimation of Perphenazine in bulk drug form - Mondal, Sumanta; Rohith Kumar, Chekka; Sai Pavan, T; Sampath, K; Vanapalli, Goutham Kumar (Journal of Drug Delivery and Therapeutics, 2019)
Perphenazine is an atypical antipsychotic drug. The simple and accurate and precise absorption ratio method has been developed for the simultaneous estimation of Perphenazine in the pure drug form. The absorption maxima were found to be 310nm in Method A (0.1N HCl Buffer) and show linearity over the concentration range of 0.002-0.02 µg/mL with regression equation y=0.5372x-0.0099(r2 = 0.9990). In Method B (Sodium acetate buffer, pH 4.5) the drug obeys Beer Lambert’s law (λmax 310nm) in the concentration range of 0.002-0.02 µg/mL with regression equation y=0.4257x - 0.0084(r2= 0.9992). In Method C (Phosphate buffer, pH 6.8) the drug obeys Beer Lambert’s law (λmax 310nm) in the concentration range of 0.002-0.02 µg/mL with regression equation y=0.482x - 0.0074(r2= 0.9991). In Method D (phosphate buffer, pH 7.2) the drug obeys Beer Lambert’s law (λmax 310nm) in the concentration range of 0.002-0.02 µg/mL with regression equation y=0.3686x - 0.0055(r2= 0.9992). In Method E (0.1N NaOH Buffer) and shows linearity over the concentration range of 0.002-0.02 µg/mL with regression equation y=0.4864x-0.0081(r2 = 0.999). In Method F (Methanol) the drug obeys Beer Lambert’s law (λmax 300nm) in the concentration range of 0.002-0.02 µg/mL with regression equation y=0.6323x - 0.003(r2= 0.999). In Method G (Ethanol ) the drug obeys Beer Lambert’s law (λmax 300nm) in the concentration range of 0.002-0.02 µg/mL with regression equation y=0.3686x - 0.0055(r2= 0.9991). First derivative spectrophotometric methods (A1, B1, C1, D1, E1, F1 and G1) were developed in 0.1NHCl and Sodium acetate pH 4.5 and phosphate buffer, in pH 6.8 and phosphate buffer, pH 7.2, 0.1N NaOH Buffer, which Perphenazine obeys Beer Lambert’s law(λmax310nm) in the concentration range of 0.002-0.02 µg/mL and 0.002-0.02 µg/mL and 0.002-0.02 µg/mL and 0.002-0.02 µg/mL and0.002-0.02 µg/mL with regression equations y=0.0357x - 0.0006 and y=0.0201x+0.0004 and y=0.0196x-0.0002 and y=0.0162x+0.0002 and y=0.0239x - 0.0002 and Perphenazine obeys Beer Lambert’s law(λmax300nm) for methanol and ethanol in the concentration range of 0.002-0.02 µg/mL and 0.002-0.02 µg/mL with regression equations y=0.0423x-0.0003 and y=0.0371x+0.0003 respectively.